2018
DOI: 10.1016/j.healun.2017.09.027
|View full text |Cite
|
Sign up to set email alerts
|

End-stage renal disease after pediatric heart transplantation: A 25-year national cohort study

Abstract: ESRD after pediatric HTx is more prevalent in HTx survivors than documented by a transplant database alone. A number of factors develop at or after HTx that increase the risk for developing ESRD. Use of KTx in post-HTx ESRD is associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…However, considering the controversy about the risks/benefits of BXM induction, the minimal effect of BXM decreasing the absolute risk of acute rejection reported by several authors 40 42 , together with the detrimental effect on Tregs shown in our study, cast doubt on the overall usefulness of BXM in pediatric heart transplantation. A recent large registry study employing multivariable models investigated the benefits of induction therapy in a cohort of pediatric heart transplanted patients after risk stratification 43 . Castleberry et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the controversy about the risks/benefits of BXM induction, the minimal effect of BXM decreasing the absolute risk of acute rejection reported by several authors 40 42 , together with the detrimental effect on Tregs shown in our study, cast doubt on the overall usefulness of BXM in pediatric heart transplantation. A recent large registry study employing multivariable models investigated the benefits of induction therapy in a cohort of pediatric heart transplanted patients after risk stratification 43 . Castleberry et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that 3% of patients required dialysis in the first post‐transplant year is higher than those reported in earlier pediatric cohorts but lower than that reported by contemporary single‐center studies of broader HT populations . Linking the Scientific Registry of Transplant Recipients (SRTR) and United States Renal Data System datasets, Choudhry et al recently reported the need for dialysis occurred in 4% of pediatric heart transplant patients over an 11.8‐year follow‐up period and that having a history of VAD support was nearly twice as common in patients who did not require dialysis . Further study is required to better understand the risk factors for dialysis after HT in this population.…”
Section: Discussionmentioning
confidence: 99%
“…ESKD was seen in 3% (n = 426) over a median follow‐up of 6.2 years. Choudhry et al 5 also looked at the SRTR and USRDS databases and reported that 4% heart transplant recipients developed ESKD over a median follow‐up of 11.8 years. The actuarial risk of developing ESRD 10 and 20 years post‐heart transplant was 3%, and 16%.…”
Section: Introductionmentioning
confidence: 99%